The Effect of Changes in Border Regimes on Border Regions Crime Rates: Evidence from the Schengen Treaty - Malte Sandner; Pia Wassmann (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2018)
In recent years many countries increased border controls, partly in response to public concerns that open borders are favoring cross-border crime. Despite these widespread concerns, empirical research on whether public fears are justi ed is still scarce. This article evaluates whether the abolishment of border controls at the eastern German and Austrian borders accompanying the implementation of the Schengen Treaty in December 2007 increased crime rates in border counties of these countries. Based on official crime statistics, conditional difference-in-differences estimation allows the evaluation of border controls in a causal way. Results show that in Germany and Austria only for burglaries a significant positive effect can be observed suggesting that for this type of criminal offense, public concerns proved to be justified. In contrast, for overall crime rates as well as for other common types of crime against property no significant effect can be observed, indicating that there is only little empirical evidence for the widespread concerns about public security.
Keywords: K42; R10; 330; Crime Rates; Border Regions; Schengen Treaty; Open Borders